Marketing Analysis of Barracuda Fish Pempek (Case Study of DapurMakassar) in Makassar City - Muh Sawir; Andi Nadia Mughsita Sani; Muh Afif Bahda (Jurnal Studi Perikanan Berkelanjutan, 2026)
This study aims to analyze the marketing system of barracuda fish pempek at Dapur Makassar, a small-scale fisheries-based enterprise located in Makassar City. The research focuses on identifying marketing channels, calculating marketing margins, and evaluating marketing efficiency. A case study method was applied using both quantitative and qualitative approaches. Primary data were collected through observation, interviews, questionnaires, and documentation involving the business owner and resellers, while secondary data were obtained from relevant literature and institutional reports. The findings show that Dapur Makassar utilizes two marketing channels: direct sales from producer to consumers and indirect sales through resellers. The direct channel incurs lower marketing costs (Rp 595.7) compared to the reseller channel (Rp 1,716.7). However, reseller distribution expands market reach beyond Makassar to other regions such as Kendari, Palu, Kalimantan, and Java. The marketing margin in the reseller channel is Rp 10,000 per unit (buying price Rp 25,000 and selling price Rp 35,000. This study concludes that combining direct marketing with organized reseller networks and digital marketing strategies can improve both efficiency and competitiveness of fisheries-based SMEs.